MODERNISASI PESANTREN: PERGESERAN TRADISI DAN PUDARNYA KYAI - Anwar, HM, Muhammad (Hunafa: Jurnal Studia Islamika, 2013)
Abstract. This paper is aimed at studying the bias of the pesantren orientation, pesantren transformation and its implication on the institutional development of the pesantren. The findings give indication that this educational institution has, slowly but surely, been unable to realize its identity as the agent of social changes. At the same time, young generation who are graduates of both general and Islamic high schools and universities have begun to play a strategic role in the management and leadership of pesantren in particular and ummah in general. Therefore, it is essential for pesantren to understand the basic idea of modernization in education. With this knowledge, pesantren will be able to make some revision toward the. ideal form of pesantren in the future.Kata kunci: pesantren, modernisasi, kyai, tradisi